INFLUENCE OF PRODUCTS, BRAND IMAGE AND SERVICES ON CUSTOMER SATISFACTION PT. PEGADAIAN BRANCH LAMONGAN - Dewi Zuliani; Imam Trisno Edy; Puguh Cahyono (Sean Institute, 2022)
This study aims to determine the effect of product, brand image and service on customer satisfaction at PT. Pegadaian Cabang Lamongan. The analytical tools used are validity test, reliability test, correlation test, multiple linear regression test, t test, F test and determination test. The sample obtained by calculating the Slovin formula was 87 respondents. The method of data collection is using a questionnaire. The results of the t-test resulted in product variables (X1) 4,310 > Ttable 1,988, brand image (X2) 4,159 > T table 1,988, service (X3) 3,141 > t table 1,988. So it is known that the three X variables have a partial effect on the Y variable. The F test produces a Fcount value of 36,293 > Ftable 3,10 so that the product, brand image and service variables together have a significant effect on customer satisfaction.